ACE2 polymorphism and susceptibility for SARS-CoV-2 infection and severity of COVID-19. Issue 8 (14th May 2021) - Möhlendick, Birte; Schönfelder, Kristina; Breuckmann, Katharina; Elsner, Carina; Babel, Nina; Balfanz, Paul; Dahl, Edgar; Dreher, Michael; Fistera, David; Herbstreit, Frank; Hölzer, Bodo; Koch, Michael; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: The RNA virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for coronavirus disease 2019 (COVID-19). Cell entry is mediated by the human angiotensin-converting enzyme II (ACE2). ACE2 and its close homolog angiotensin-converting enzyme I ( ACE ) are currently discussed candidate genes, in which single-nucleotide polymorphisms (SNPs) could alter binding or entry of SARS-CoV-2 and enhance tissue damage in the lung or other organs. This could increase the susceptibility for SARS-CoV-2 infection and the severity of COVID-19. Patients and methods: We performed genotyping of SNPs in the genes ACE2 and ACE in 297 SARS-CoV-2-positive and 253 SARS-CoV-2-negative tested patients. We analyzed the association of the SNPs with susceptibility for SARS-CoV-2 infection and the severity of COVID-19. Results: SARS-CoV-2-positive and SARS-CoV-2-negative patients did not differ regarding demographics and clinical characteristics. For ACE2 rs2285666, the GG genotype or G-allele was significantly associated with an almost two-fold increased SARS-CoV-2 infection risk and a three-fold increased risk to develop serious disease or COVID-19 fatality. In contrast, the ACE polymorphism was not related to infection risk or severity of disease. In a multivariable analysis, the ACE2 rs2285666 G-allele remained as an independent risk factor for serious disease besides the known risk factors male gender and cardiovascular disease. Conclusions: In summary, our report appears to be the first showing that a common ACE2 polymorphism impacts the risk for SARS-CoV-2 infection and the course of COVID-19 independently from previously described risk factors.